Need for Activating the Desire to Learn among Learners to Raise the Quality of Education - Tripathy, K.K. (JOURNAL OF INDIAN EDUCATION, 2018)
After the implementation of the Sarva Shiksha Abhiyan (SSA), India has witnessed increased access to education at the elementary level. As a consequence, the Net Enrolment Ratio (NER) of children above the age of six years has risen to 87 per cent. But unfortunately, the quality of education has not kept pace with the quantitative expansion of education. At present, there is a learning crisis in India. Therefore, there is an urgent need of the country to end this crisis through a number of interventions. Effective training of both pre-service and in-service teachers is crucial to transform the instructional process from teacher-centred to learner-centred approach. Poor student achievement is often attributed to a lack of motivation. For more than a century, a reward and punishment model has been used in all the classrooms of the world to increase student motivation. Now, there is a lot of empirical evidence that external motivation in the form of reward is less effective than intrinsic motivation to improve the quality of education. Rewards do not activate desire for learning. The desire for learning is activated in the classroom learning environment if it is full of joy and excitement.